Monitoring closed circuit television in Telkom University Landmark Tower using internet of things - Oktavianingrum, Andarista Putri; Azrika, Andi Zhagyta Amalia; Fathurrahman, Muhammad Naufal; Usman, Uke Kurniawan; Hambali, Akhmad (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2025)
This research develops a prototype Closed Circuit Television (CCTV) monitoring system within a university building for remote access using Internet of Things (IoT) technology. Addressing the growing need for security surveillance on campuses, the study uploads processed videos from the Network Video Recorder (NVR) to a Virtual Private Server (VPS), facilitating real-time CCTV monitoring through a website. UiPath, employed for Robotic Process Automation (RPA), automates commands, and the system stores processed video data in its database.The research results indicate that this system is capable of providing effective CCTV monitoring with real-time access through the website. Quantitative data shows user satisfaction survey with a success rate above 40%, answering "Agree" and "Strongly Agree" to each survey question. Website security testing was also conducted, achieving a 100% reliability and availability level for MFA technology. In conclusion, the prototype of this system successfully addresses the challenges encountered in remote CCTV monitoring at Telkom University Landmark Tower. Users can access the website through smartphones or computers connected to the internet.